2009
DOI: 10.1021/jp808713m
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Substitution in Bioactive Calcium Phosphates: A First-Principles Study

Abstract: First-principles calculations are performed to investigate atomic and electronic structures of Sr(2+) ions substituting for Ca(2+) in octacalcium phosphate (OCP). The defect formation energies are evaluated from total energies of supercells and ionic chemical potentials of Sr(2+) and Ca(2+) determined under the chemical equilibrium with aqueous solution saturated with hydroxyapatite (HAp). The defect formation energy depends on the solution pH and the substitutional Ca sites in OCP, and the estimated equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
6
30
1
1
Order By: Relevance
“…This, however, relates to 0K and do not include a stabilizing free energy term, -TΔS, provided by the entropy of mixing at finite temperature. The Excess Energies from this work are consistent with those of Terra et al 13 and Matsunaga and Murata, 14 where a similar Site I preference for the doping at 0K has been observed.…”
Section: Ab-initio Simulationssupporting
confidence: 90%
“…This, however, relates to 0K and do not include a stabilizing free energy term, -TΔS, provided by the entropy of mixing at finite temperature. The Excess Energies from this work are consistent with those of Terra et al 13 and Matsunaga and Murata, 14 where a similar Site I preference for the doping at 0K has been observed.…”
Section: Ab-initio Simulationssupporting
confidence: 90%
“…Collin [1959] also demonstrated that a0 and c0 lattice constants increase linearly with Sr substitution, which was supported by other studies [Lagergren and Carlström, 1957;Schoenberg, 1963;LeGeros et al, 1977;Okayama et al, 1991;Markovic and Brecevic, 1992]. Pan et al [2009b] [Matsunaga and Murata, 2009].…”
Section: Sr and Capisupporting
confidence: 76%
“…Bachra and Fischer [1969] reported that Sr can slow down HAp crystal growth, which was supported by other studies for HAp [Koutsoukos and Nancollas, 1981;Christoffersen et al 1997;Verberckmoes et al, 2004], for ACP [Root, 1990;Hidaka et al, 1991], for ACP to OCP to HAp conversions [Markovic and Brecevic, 1992], and for the α-tricalcium phosphate to HAp conversion [Boanini et al, 2010]. Bigi et al [1988] suggested that Sr does not 'greatly affect' the conversion of OCP and BR into HAp, but stilland to a lesser extent than Mg. Sr can, however, also be seen to stabilize HAp precursor phases [Matsunaga and Murata, 2009] and therefore to increase the number of biological nucleation sites [Drouet et al, 2008]. Pan et al [2009b] also postulated that nucleation of SrHAp is easier than HAp, and that this may act as a template for HAp growth.…”
Section: Sr and Capimentioning
confidence: 99%
“…While Sr incorporation into the apatite lattice causes an expansion in both a-and c-axes 26 due to Sr's larger atomic radius, 27 leading to higher apatite solubility, 12 Sr has also the ability to stabilize apatite pre-cursor phases, such as OCP. 28 Furthermore, Pan et al 13 postulated that nucleation of Sr-substituted apatite is easier than that of apatite, and that this may act as a template for apatite growth. This would explain the results of Thuy et al, 14 who demonstrated enhanced in vitro remineralization of caries lesions in the presence of Sr and F compared to F alone.…”
Section: 2)mentioning
confidence: 99%